Agendas, alternatives, and public policies - Kingdon, John W. (Longman, 1995)
This text remains the authoritative work on agenda setting and policy formation. This report on original research includes many dow-to-earth illustrations and quotations from interviews, creating enjoyable and informative reading for undergraduate students